National Educational Policies of India: : Inclusion in ECCE - Bala, Ritu; Parul; Sharma, Radhika (THE PRIMARY TEACHER, 2025)
Young children need to be exposed to a variety of environments; they also need to interact with individuals from different backgrounds, castes, regions, disabilities, giftedness, etc. This would, on one hand, make the children aware of the different types of people around them and on the other hand, make marginalised and vulnerable children not feel left out in educational spaces. Inclusion in education is viewed differently in different parts of the world. Inclusive education is concerned with removing all the barriers to learning with the participation of all learners vulnerable to exclusion and marginalisation (Kaga and Sretenov, 2021, p. 6). This research attempts to explore inclusion in Early Childhood Care and Education (ECCE) from an Indian perspective in light of the National Education Policies of 1968, 1986 and 2020. In addition, this paper attempts to investigate numerous barriers in the implementation of inclusive ECCE. This paper is based on secondary data and for this purpose, national documents on ECCE and diverse literature have been analysed